Construction of Organizational Climate Scale for a Public Organization - Thâmara Dayane Cardoso Santos; Mariana dos Santos Rodrigues; Leilane Pereira de França; Bruno Kaipper Ceratti; Pedro Paulo Murce Meneses (Revista Psicologia)
This study aimed to construct an Organizational Climate Scale for a public organization. The construction of the scale had three phases: definition of the factors that would be tested; elaboration of the items; and validation of the items. The samples were composed by 5 public servants from the sector (semantic analysis); 3 judges who were organizational climate researchers; 16 public servants from the institution; and 260 public servants who answered the questionnaire. The instrument had 39 items and 6 variables, and was analyzed using exploratory factor analysis. The final scale consisted of 29 items and 5 factors. These factors explain 64.90% of the variance of the construct and attained a Cronbach’s alpha between 0.84 and 0.95. The results indicated evidence of the validity, reliability, and internal consistency of the instrument.